Training on Making Local Microorganisms (MOL) based on Mimosa Roots to Farmers Group in Jubung Village - Harsanti, Restiani Sih; Fariroh, Indri; Usmadi; Eriani Munandar, Denna; Sundahri; Stephani Pakpahan, Tioma; Aritonang, Firman (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Jubung Village is the largest soybean producer in Sukorambi District. Partners in this service are farmer groups in Jubung with the name of the Farmer Group "Tani Mulyo". This partner has the problem of soybean production that cannot increase and the high price of fertilizer. The solution offered to solve the problem is the use of local Microorganisms (MOLs). MOL is useful for increasing plant production and bio activators and fermentation of animal feed. Mimosa has the potential as an antimicrobial food pathogen. Mimosa root can speed up the process of absorption of nutrients and water, as well as remodel organic matter in the soil. The purpose of the service activity is to introduce the technology of making root MOL to supporting organic farming. The solutions provided will be divided into several activities, including socialization, counseling about the role of PGPR and MOL, soybean cultivation according to GAP, practices for making Root MOL, monitoring and evaluation. The results of the activity showed that the participants participated in the activity enthusiastically, as evidenced by the discussion that went well. The indicators of the success of making MOL are indicated by the characteristics of cloudy color and have a fermentation smell